2012
DOI: 10.1109/tpwrs.2012.2184308
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Multiobjective Optimization of Kernel-Based Very-Short-Term Load Forecasting

Abstract: A useful tool for the efficient management of the electric power grid is the accurate, ahead-of-time prediction-of-load demand. A novel methodology for very-short-term load forecasting is introduced in this paper, and its performance is tested on a set of historical, demand-side, 5-min data. The approach employs an ensemble of kernel-based Gaussian processes (GPs) whose predictions constitute the terms of a linear model. Adoption of a set of cost functions assessing model accuracy allows the formulation of a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…In fact, power demand also needs to be considered as an uncertain parameter, but in comparison to the wind power, its demand value is more predictable in the application of online optimization. Many approaches have been developed for very short-term load forecasting aiming at prediction ranges of a few minutes to an hour [32][33][34][35]. In [32], it is shown that the mean absolute percentage error (MAPE) can be less than 0.2% for a 120-s prediction horizon.…”
Section: Problem Formulationmentioning
confidence: 99%
“…In fact, power demand also needs to be considered as an uncertain parameter, but in comparison to the wind power, its demand value is more predictable in the application of online optimization. Many approaches have been developed for very short-term load forecasting aiming at prediction ranges of a few minutes to an hour [32][33][34][35]. In [32], it is shown that the mean absolute percentage error (MAPE) can be less than 0.2% for a 120-s prediction horizon.…”
Section: Problem Formulationmentioning
confidence: 99%
“…Alamaniotis et al proposed an evolutionary multiobjective optimization algorithm to predict a five-minute load [9], but the predicted time is too short to fit the need. Some literatures used wavelet neural networks to predict a short-term load forecasting [10] and [11], but this method introduces too much computation overhead and thus affects its feasibility.…”
Section: Related Workmentioning
confidence: 99%
“…For VSTLF, Taylor used the observations of minute-by-minute British electricity demand to evaluate various methods including autoregressive integrated moving average (ARIMA) models and two exponential smoothing methods [9]. Alamaniotis et al proposed an ensemble of kernel-based Gaussian processes [10]. Guan et al pre-filtered the spikes in load series and decomposed the load series using wavelet prior to feeding it into a neural network [11].…”
Section: Introductionmentioning
confidence: 99%